Participação como Representação: O Impacto das Conferências Nacionais de Políticas Públicas no Congresso Nacional - Thamy Pogrebinschi; Fabiano Santos (Universidade do Estado do Rio de Janeiro, 2011)
The relationship between representative democracy and participatory and deliberative experiences is not trivial. Those who endorse the discourse of a crisis in political representation sometimes defend participatory and deliberative modalities of democracy as a way of denying the legitimacy of the Legislative Branch, questioning the latter's real capacity to express the people's sovereign will. Still, the emergence of new democratic spaces, as well as new actors involved in the management of the public good, can be seen as a way of strengthening political representation, and not as a sign of weakening in its institutions. The current article defends this argument, seeking to demonstrate that the Brazilian national conferences on public policy have actually provided impetus to the National Congress, thereby strengthening representative democracy in Brazil through a participatory and deliberative practice.